TRANSNATIONAL LABOR MIGRATION AND ITS IMPACT ON SOCIAL AND ECONOMIC INEQUALITIES: A GLOBAL LEGAL PERSPECTIVE - Asadov Davlatbek (International Journal of Economic Integration and Regional Competitiveness, 2024)
Background: Transnational labor migration is a significant phenomenon that influences social and economic inequalities on a global scale. Specific Background: This article focuses on the intricate relationship between labor migration and inequalities, examining how international laws and agreements shape national labor migration policies and their implications for migrants' rights and socio-economic outcomes. Knowledge Gap: Despite extensive discourse on labor migration, there remains a limited understanding of the specific ways in which legal frameworks either address or exacerbate inequalities faced by migrants. Aims: The study aims to analyze various legal instruments and their effectiveness in mitigating inequalities arising from labor migration, using a range of case studies to illustrate these dynamics. Results: The findings reveal that existing international legal frameworks often fail to provide adequate protection for vulnerable migrants, thereby perpetuating socio-economic disparities. Furthermore, while some legal instruments aim to promote equity, their implementation remains inconsistent across different regions. Novelty: This research contributes to the literature by offering a global legal perspective that emphasizes the role of legal instruments in shaping migration outcomes and highlights the nuanced ways in which these laws can influence inequality. Implications: The study underscores the urgent need for comprehensive legal reforms and enhanced regional cooperation to protect the rights of migrants and to mitigate the adverse effects of labor migration on marginalized populations. By doing so, it advocates for a more equitable framework that supports both migrants and the communities they engage with.